Influence of aprepitant on the pharmacodynamics and pharmacokinetics of gliclazide in rats and rabbits - Kura, Raghunandan Reddy (PeerJ, 2018)
BACKGROUND: Concomitant drug administration is a general phenomenon in patients with chronic diseases such as diabetes mellitus. Among the currently available oral antidiabetic drugs, gliclazide is a commonly prescribed drug considering its multiple benefits in diabetic patients. Aprepitant is a commonly prescribed antiemetic drug which is mainly metabolized by CYP3A4, reported to have modest inductive and inhibitory effects on CYP2C9 and CYP3A4, respectively. Since gliclazide is metabolized by CYP2C9 (major) and CYP3A4 (minor), it is very difficult to predict the influence of aprepitant and its metabolic interaction with gliclazide. Considering the complexity associated with the combination of aprepitant and gliclazide, this study was designed to evaluate the influence of aprepitant on the pharmacodynamics (PD) and pharmacokinetics (PK) of gliclazide in animal models. METHODS: The PD interaction studies were conducted in both rodent (normal and alloxan-induced diabetic rats) and non-rodent (rabbits) animal models (n = 6) while the PK interaction study was conducted in normal rabbits (n = 6). An extrapolated human therapeutic oral dose of gliclazide, aprepitant and their combination were administered to rats and rabbits with 7 days washout between each treatment. For the multiple-dose interaction study, the same groups were administered with an interacting drug (aprepitant) for 7 days and then the combination of aprepitant and gliclazide on the 8th day. From the collected animal blood samples, blood glucose (by Glucose-Oxidase/Peroxidase method), insulin (by ELISA method) and gliclazide concentration levels (by HPLC method) were determined. Non-compartmental PK analysis was conducted by Phoenix WinNonlin software to determine the PK parameters of gliclazide. Statistical analysis was performed by student’s paired t-test. RESULTS: The pharmacodynamic activity (blood glucose reduction and insulin levels) of gliclazide was significantly (p < 0.05) influenced by aprepitant in normal and diabetic condition without any convulsions in animals. There was a significant (p < 0.05) increase in concentration levels and Area Under the Curve of gliclazide while significant (p < 0.05) decrease in clearance levels of gliclazide in rabbits. The PK interaction with gliclazide is relatively more with the multiple dose treatment of aprepitant over single dose treatment. CONCLUSION: In combination, aprepitant significantly influenced the pharmacodynamic activity of gliclazide in animal models. Considering this, care should be taken when this combination is prescribed for the clinical benefit in diabetic patients.